Extreme capital breeding for giants: Effects of body size on humpback whale energy expenditure and fasting endurance - Fredrik Christiansen; Peter T Madsen; Virginia Andrews-Goff; Mike C Double; Jason R How; Phil Clapham; Yulia Ivashchenko; Dmitry Tormosov; Kate R Sprogis (Ecological Modelling, 2025)

Gear modifications reduced humpback whale entanglements in a commercial rock lobster fishery - Jason R. How; William K. de la Mare; Douglas K. Coughran; Michael C. Double; Simon de Lestang (Marine Mammal Science, 2021)
Entanglement of whales in fishing gear occurs globally and where populations are recovering from past exploitation, entanglement frequency is likely to increase. The Western Australian population of humpback whales ( Megaptera novaeangliae ) is growing rapidly, yet from 1990 to 2010 the number of whales reported entangled in gear from the pot‐based western rock lobster fishery was relatively stable at around one per year. However, from 2010, reported entanglements increased, reaching a maximum of 17 in 2013. This increase occurred immediately after a shift to a year‐round quota‐based fishery that eliminated the annual 4½‐month closure that coincided with the whale migration. Gear modifications that eliminated surface rope, shortened rope lengths, and reduced float numbers were implemented in June 2014 to reduce whale entanglements. The effectiveness of these modifications was evaluated using a Bayesian model that incorporated changes in humpback whale population size, entanglement reporting probability, fishing effort, and whale migration timing. Our analyses indicate that gear modifications reduced entanglement in fishing gear from the rock lobster fishery by at least 25% (with 95% probability), with a median reduction of 64%. The model also showed that the greatest entanglement risk occurs on the northward migration and in water depths of 55–73 m.

Macrophage expression of tartrate-resistant acid phosphatase as a prognostic indicator in colon cancer - Joan How; Jason R. Brown; Sasha Saylor; David L. Rimm (Histochemistry and Cell Biology, 2014)